Establishment of Semal Seed Orchard at RaniPur (Hardwar), U.P. - Tiwari, K. M. (Indian Forester, 1970)
In order to produce genetically superior seeds to meet the demand of seed for raising plantations of Semal (Bombax ceiba), the first seed orchard of this spp. has been successfully established at Ranipur about 75 km S.E. of Dehra Dun in co-operation with the Genetics Branch of Forest Research Institute, Dehra Dun. The technique of its raising, the practical difficulties encountered, and the quantum of success obtained to-date is described in some detail in this article.